Hukum Hadat Dayak Ngaju: Tahiu Janji Pangawin di Kalimantan Tengah - Muhamamd Dlaifurrahman; Akhmad Fauzi Aseri; Mujiburohman Mujiburohman (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
The purpose of this study is to find out how the Ngaju Dayak Hadat Law regulates the application of tahiu promise pangawin to the Ngaju Dayak indigenous people. The method that the author uses is a normative research method with a library study approach, using primary and secondary legal materials such as 96 articles of Damai Tumbang Anoi, the book of Panaturan, marriage agreements, legal books and legal research results. The results of this study that know the promise of pangawin is a customary law of the Ngaju Dayak community to form an eternal household but only death can separate because for the Ngaju Dayak indigenous people marriage is a sacred and sacred thing, it is very necessary to maintain its sanctity. In accordance with the teachings they believe, referring to the marriage stories between Raja Garing Hatungku and Nyai Endas Bulau Lisan Tingang in the book of Panaturan chapter 30. For those who violate the promise of marriage, they will be subject to sanctions in accordance with article 3, namely singer hatulang not yet in the 96 articles of Peace. Fall Anoi.